Description of the free-swimming juvenile stages of Lernaeocera branchialis (Pennellidae), using traditional light and confocal microscopy methods. - Brooker, A.J., J.E. Bron & A.P. Shinn (Aquatic Biology, 2012)
The last detailed morphological descriptions of the juvenile stages of the parasitic copepod Lernaeocera branchialis (L., 1767) were written more than 70 yr ago, since which time both taxonomic nomenclature and available imaging technologies have changed substantially. In this paper a re-description of the free-swimming juvenile stages of L. branchialis is presented using a combination of traditional light microscopy and modern laser scanning confocal microscopy (LSCM) techniques. Detailed descriptions are provided of the nauplius I, nauplius II and copepodid stages and comparisons are made with the findings for other siphonostomatoids. Nauplius II is previously undescribed and several structures are described at the terminal tip which have not been found in other pennellids. With renewed interest in L. branchialis as a result of expanding gadoid aquaculture in North Atlantic countries, this re-description provides im- portant information on its life history that may be useful for further research into this potentially devastating pathogen.